2018
DOI: 10.1080/19338244.2018.1434474
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to sulfur dioxide and mortality: Historical data from Yokkaichi, Japan

Abstract: We examined the association between acute exposure to sulfur dioxide (SO) and mortality, using historical data from 1972-1991 in Yokkaichi, Japan. We used a time-stratified case-crossover study design. We included all causes of death, excluding external causes, between 1972 and 1991 in Yokkaichi and the neighboring town, Kusu of the Mie Prefecture (N = 29,839). We obtained daily estimations of SO concentrations during the study period. We then conducted conditional logistic regression analysis to examine assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In this study, the association between the SO 2 concentration and the respiratory inpatient visits was stable after adjusting for other air pollutants at lag4. A study in Japan by Yorifuji et al ( 42 ) also suggested that the relationship between SO 2 exposure and respiratory system mortality can still be observed after adjusting for atmospheric pollutants, such as nitrogen dioxide and particulate matter. Yang et al ( 43 ) proposed that multi-pollutant models increase the standard error, so the effects of multi-pollutant models tend to be slightly lower than those of single-pollutant models, which was consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the association between the SO 2 concentration and the respiratory inpatient visits was stable after adjusting for other air pollutants at lag4. A study in Japan by Yorifuji et al ( 42 ) also suggested that the relationship between SO 2 exposure and respiratory system mortality can still be observed after adjusting for atmospheric pollutants, such as nitrogen dioxide and particulate matter. Yang et al ( 43 ) proposed that multi-pollutant models increase the standard error, so the effects of multi-pollutant models tend to be slightly lower than those of single-pollutant models, which was consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have revealed that if people are exposed to SO 2 for a long time, the upper respiratory tract is stimulated, bronchial smooth muscle is contracted, respiratory resistance is increased, and respiratory functions decrease. SO 2 increases and thickens the secretion of respiratory mucosa hinders the movement of cilia, weakens immune function, reduces the resistance of the respiratory tract, induces inflammation to varying degrees, and leads to mental retardation [46][47][48][49].…”
Section: The Effects Of Air Pollution Intensity and Pollutantsmentioning
confidence: 99%
“…A comprehensive demonstration of the history of Yokkaichi Asthma and the related countermeasures was given by Yukimasa et al [22]. The past dataset of Yokkaichi was examined many times to prove that SO 2 exposure increases the risk of all-cause and cause-specific mortality [23]. Air pollution incidents in multiple Chinese cities were also mentioned in the study of K. Yoshida as a comparison with Yokkaichi.…”
Section: So 2 Pollution In Japan and Chinamentioning
confidence: 99%